"Guys, we have a genius here”: the co-construction of linguistic-discursive violence in an interaction on Twitter - Albuquerque, Rodrigo; Sousa, Ana Luiza Nogueira (Revista Letras Raras, 2022)
In this work, we aim to analyze how two internet users, based on a post by the Ministry of Health on their Twitter profile, use, in their argumentation, impoliteness strategies to promote mutual linguistic-discursive violence. In the theoretical framework, we articulate the studies of (im)politeness, inscribed in micro/linguistic, macro/sociodiscursive and meso/sociointeractional domains, and the studies of argumentation, focusing on eristic argumentation, considering its intrinsic relationship with linguistic-discursive violence. In the methodological framework, we chose to conduct a netnographic study, inscribed in an exclusively qualitative episteme. We selected and analyzed texts related to an online-mediated interaction on Twitter that had a conflicting character and that discussed hydroxychloroquine as an early treatment strategy in the fight against COVID-19. In the analytical framework, we emphasize that, in general, impoliteness became gradually more intense between the internet users, establishing an eristic argumentation, permeated by ad hominem and ad personam arguments, in the co-construction of metapragmatics of linguistic-discursive violence. We believe that it is beneficial for institutional profiles to institute policies to moderate such interlocutions, encouraging constructive and aggregating dialogues.